A gain-of-function NLRP3 3′-UTR polymorphism causes miR-146a-mediated suppression of NLRP3 expression and confers protection against sepsis progression - Furong Lu (Nature Portfolio, 2021)
Abstract Nucleotide-binding domain and leucine-rich repeat (LRR)-containing family protein 3 (NLRP3) regulated the maturation of inflammation-related cytokines by forming NLRP3 inflammasome, which plays pivotal roles in sepsis pathogenesis. In this study, we evaluated the genetic association of NLRP3 polymorphisms with sepsis (640 patients and 769 controls) and characterized the impact of NLRP3 polymorphisms on NLRP3 expression and inflammatory responses. No significant differences were observed in genotype/allelic frequencies of NLRP3 29940G>C between sepsis cases and controls. The G allele was significantly overrepresented in patients with septic shock than those in sepsis subgroup, and the GC/GG genetypes were related to the 28-day mortality of sepsis. Lipopolysaccharide challenge to peripheral blood mononuclear cells showed a significant suppression of NLRP3 mRNA expression and release of IL-1β and TNF-α in CC compared with the GC/GG genotype category. Functional experiments with luciferase reporter vectors containing the NLRP3 3′-UTR with the 29940 G-to-C variation in HUVECs and THP-1 cells showed a potential suppressive effect of miR-146a on NLRP3 transcription in the presence of the C allele. Taken together, these results demonstrated that the 29940 G-to-C mutation within the NLRP3 3′-UTR was a gain-of-function alteration that caused the suppression of NLRP3 expression and downstream inflammatory cytokine production via binding with miR-146a, which ultimately protected patients against susceptibility to sepsis progression and poor clinical outcome.